Knowledge Mapping Analysis of International Communication in Chinese Higher Education: A Visualization Study Based on CiteSpace - Chen , Yu; Huang, Zhiying (The Journal of Medicine, Humanity and Media, 2026)
International communication in Chinese higher education plays a pivotal role in facilitating cross-cultural exchange, enhancing China's global discourse influence, and advancing national strategic objectives. This study employs CiteSpace bibliometric visualization to systematically analyze scholarly literature on international communication research in Chinese higher education from 2010 to 2024. Four key findings emerge from this analysis: (1) Research activity has evolved through distinct phases, demonstrating a marked intensification after 2021, with concentrated attention on themes including "Telling China's Story Well," emerging foreign language pedagogies, and strategic talent cultivation; (2) Research priorities have shifted in alignment with evolving national strategies, progressing from foreign language education frameworks to international communication capacity building, and subsequently to the construction of a discourse system for Chinese modernization; (3) The field exhibits increasing interdisciplinary characteristics, yet remains constrained by insufficient cross-disciplinary integration and fragmented scholarly efforts; (4) Inter-institutional collaboration networks remain structurally dispersed, hindering the formation of systematic theoretical innovation communities. This research provides a comprehensive knowledge landscape for theoretical development and practical innovation in international communication within Chinese higher education, offering empirical foundations to advance scholarly inquiry in this domain.